PERSEPSI ULAMA TENTANG ZAKAT PRODUKTIF DIKOTA BANJARMASIN - Abdullah; Elida Mahriani; Sri Anafarhanah (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: Poverty is a multidimensional problem that can be caused by several reasons, generally causedby economic problems. From the survey results of BPS South Kalimantan per September 2014 wasrecorded that poverty in South Kalimantan Province is 4.68% (62.509 people) of South Kalimantanpopulation, 3.790.071 people. From these, especially the poor in the city of Banjarmasin recorded 28.59million people (11.66%). In addition to government programs to reduce poverty, one of the solutionsthat can be utilized in the perspective of Islam is zakat leverage, particularly productive zakat. Tomove this productive charity needs to be synergy and synchronization of the various parties, in this caseare: the Government, the Ministry of Religious Affairs, the Indonesian Ulema Council (MUI), and theOrganization of the Islamic Religious including more specific ie BAZNAS. With the synergy and syn-chronization of the various parties, it is certain the collection and distribution of zakat, especiallyproductive zakat, would be more efficient and effective to support the prevention and alleviation ofpoverty and to achieve welfare for the people.